Peran Kepala Sekolah Dalam Meningkatkan Kinerja Guru, Iklim Organisasi, dan Mutu Pendidikan di SMAN Se-Lampung Tengah - Husnul Mu'amalah (MKKS SMA, MKKS SMP se-Kota Metro, Persatuan Sarjana Pendidikan Islam Wilayah Provinsi Lampung, dan CV.IQRO Penerbitan, 2020)
Quality education management is inseparable from the ability of the principal. The principal as a leader in his work unit must be accompanied by several qualifications attached to his duties and functions. The type of research used in this research is descriptive qualitative. In this research, it is attempted to collect as much descriptive data as possible which will be stated in the form of reports and descriptions. Based on this objectively, the type of descriptive research used is a case study. The results of this study regarding the role of school principals in improving teacher performance, organizational climate and quality of education have not been successful due to the absence of maximum cooperation between the government and the environment. Therefore, good relations from all parties must be maintained so as to assist the role of the principal in improving teacher performance, organizational climate and quality of education.